Different profiles of naturally produced and anthropogenic organohalogens in the livers of cetaceans from the Sea of Japan and the North Pacific Ocean. (November 2018) - Fujii, Yukiko; Kato, Yoshihisa; Kozai, Mai; Matsuishi, Takashi; Harada, Kouji H.; Koizumi, Akio; Kimura, Osamu; Endo, Tetsuya; Haraguchi, Koichi
Abstract: Levels and profiles of naturally produced halogenated bipyrroles (Br4 Cl2 -DBP and Cl7 -MBP), methoxylated tetrabromodiphenyl ethers (6-MeO-BDE47), anthropogenic perfluoroalkyl substances (PFASs) and legacy persistent organic pollutants (POPs) were investigated in the livers of 14 cetaceans from the Sea of Japan and the North Pacific Ocean. The concentrations of Br4 Cl2 -DBP (4 to 4900 ng/g-wet), Cl7 -MBP (16 to 3960 ng/g-wet) and 6-MeO-BDE47 (7 to 190 ng/g-wet) were higher in the order of killer whales > toothed whales > baleen whales. Profiles of PFASs were dominated by perfluoroundecanoic and perfluorotridecanoic acids (10 to 540 ng/g-wet), sum of which accounted for 70% of total measured PFASs. Regional difference was observed for Cl7 -MBP and PFASs, which were higher in the Sea of Japan, whereas Br4 Cl2 -DBP was in the North Pacific Ocean. Specific accumulation pattern of these natural contaminants in cetaceans around northern Japan could help compare the exposure profile of PFASs and POPs among other geographic regions. Graphical abstract: Highlights: Halogenated bipyrroles and methoxy-PBDEs accumulated in the livers of cetaceans. Long-chained perfluoroalkyl carboxylates (PFCAs) largely exceeded the sulfonates. No correlation was detected between natural products and long-chain PFCAs. Bipyrrole and long-chain PFCA profiles differed in cetaceans from two regions.